Results of a nationally implemented cardiac screening programme in elite cricket players in England and Wales - MacLachlan, H.; Dhutia, H.; Bhatia, R.; Boden, K.; Forenc, K.; Basu, J.; Miles, C.; Osborne, R.; Chandra, N.; Malhotra, A.; Stuart, G.; Peirce, N.; et al. (Journal of Science and Medicine in Sport, 2022)
Objectives: We assessed the diagnostic yield and costs of an electrocardiogram-based national screening programme in elite cricket players and the incremental value of transthoracic echocardiography and periodic evaluation. Design: Cross-sectional study. Methods: Between 2008 and 2019, 1208 cricketers underwent screening with a health questionnaire, 12-lead electrocardiogram and cardiology consultation. Athletes with concerning findings underwent on-site transthoracic echocardiography and further investigations as necessary. In addition, despite a normal health questionnaire and electrocardiogram, 342 (28.3%) athletes had a transthoracic echocardiogram and 493 (40.8%) underwent repeat evaluations. Results: After initial evaluation, 47 (3.9%) athletes underwent on-site transthoracic echocardiography of whom 35 (2.8%) were referred for further evaluation. Four athletes (0.3%) were diagnosed with major cardiac conditions; hypertrophic cardiomyopathy (n = 1), arrhythmogenic cardiomyopathy (n = 1) and Wolff-Parkinson-White pattern (n = 2). Two athletes were identified with minor valvular abnormalities. Repeat evaluation of 493 athletes identified hypertrophic cardiomyopathy in a 22-year-old athlete, two years after his initial normal screening. During a follow-up of 5.8 - 2.9 years no additional diagnoses or adverse cardiac events were reported. The cost of the electrocardiogram-based programme was ?127,844, translating to 106 per athlete and 25,569 per major cardiac condition identified.Routine transthoracic echocardiography in 342 athletes identified two athletes with major cardiac conditions (bicuspid aortic valve with severe aortopathy and aortic regurgitation and an atrial septal defect associated with right ventricular volume overload) and 10 athletes with minor abnormalities. Conclusions: An electrocardiogram-based national screening programme identified a major cardiac condition in 0.3% of athletes. Routine transthoracic echocardiography and periodic evaluation increased the diagnostic yield to 0.6%, at an incremental cost.